Digital Competition in Different Sectors of the Economy - Borzenko, Olena; Hlazova, Anna (Vilnius University Open Series, 2022)
The introduction of information and communication technologies (ICT) into different sectors of the economy has led to the emergence of the digital economy, defined by the “fourth industrial revolution”. Digital competition in different sectors of the Ukrainian economy is mainly seen in the creation of digital services, while global practice demonstrates the modernization of enterprises based on digitalization of production, the sales sphere and so on.Digitization and its competition in different spheres of the national economy is studied here. Namely, it is determined that nowadays digitization of the real sector of Ukraine's economy in the form of innovative production is not observed at the moment, but digitalization is more represented in the financial sector. Taking into account the current structure of the financial market in Ukraine, it was found that digitalization processes have largely affected the banking sector, which is embodied in the presence of developed Internet banking. It is found that the stock market in Ukraine currently lags far behind the banking sector in terms of the introduction of digital technologies.
Keywords: digital economy; digitization,; real and financial sectors of the economy; digital competition